Validitas E-Modul Perubahan Iklim dan Pemanasan Global Terintegrasi Model PBL untuk Siswa SMA - Tasmiyatul Iffah; Ratnawulan Ratnawulan (Lembaga Yasin AlSys, 2026)
The development of electronic teaching materials has become an important issue in science learning, but studies that specifically discuss the development of e-modules on climate change and global warming materials integrated with the Problem Based Learning model remain limited. This study aimed to determine the validity level of the developed e-module. This study used a Research and Development (R&D) method with the 4D development model consisting of the define, design, develop, and disseminate stages. The implementation of the study was limited to the develop stage, particularly expert appraisal or validity testing by three experts as validators. The validation instrument was developed based on teaching material development guidelines, with assessment components including material substance, instructional design, visual communication, software utilization, and the suitability of the teaching materials with the learning model. The results of the validity test from the three validators showed a percentage score of 91%, which was categorized as very valid. The conclusion of this study confirms that the e-module on climate change and global warming materials integrated with the Problem Based Learning model is declared valid, so it has the potential to be used as electronic teaching material that supports problem-based learning.